Pengaruh Pengetahuan dan Penerapan Jaminan Terhadap Minat Nasabah Terhadap Produk Syirkah di Bank Syariah Kota Metro - Hasan Basri, Mohammad; Nurjannah, Siti; Swastika, Putri (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This study aims to determine the effect of knowledge and collateral on customer interest in taking syirkah products at Metro City Sharia Bank. This study uses a quantitative approach with a sample of 96 respondents and regression methods on SPSS Statistics 25. This research is descriptive while the type of research is quantitative research. The sample in this study were 96 customers of Syari'ah Bank in Metro City. The data collection method used is the questionnaire method and the documentation method. The results showed that there is a positive and significant influence between knowledge variables on customer interest and the application of guarantees to customer interest in taking Syirkah products at Sharia Banks in Metro City. Efforts are needed to increase socialization and education about Islamic bank products and syirkah contracts to the public through electronic and print media. Because of the increasing knowledge, the tendency of public interest to use Islamic bank products is increasing.